Implementation of Augmented Reality and Integrated Video as Interactive Learning Media for Mentally Disabled People in Recognizing Numbers and Letters based on the MathAlfa Application - Manurung, Asrar Aspia; Sari, Indah Purnama; Nasution, Marah Doly (Indonesian Journal of Education and Mathematical Science, 2025)
Law No. 20 of 2003 on the National Education System mandates inclusive education for children with special needs (ABK) in order to optimize their potential. However, the learning process for kids with mental retardation is hampered by the lack of new learning resources. Thus, a solution is provided by the MathAlfa program with Integrated Video Augmented Reality (AR). In addition to promoting the use of technology in inclusive education, MathAlfa is intended to improve the learning achievement, comprehension, and engagement of children with mental retardation. It is anticipated that features like materials, AR films, and quizzes that rely on visual recognition and direct interaction will be able to give students with mental retardation a more engaging, inclusive, and adaptive learning environment. One technology that has great potential in supporting learning for students with intellectual disabilities is Augmented Reality (AR). AR is a technology that combines virtual objects with real environments in real-time, providing a more immersive interactive experience. By using AR, students can interact directly with learning materials that are visualized in the form of 3D objects, videos, or animations, which can help them understand abstract concepts more concretely and visually.